Germanys Continued Productivity Slump: An Industry Analysis - Theo S. Eicher; Thomas Strobel (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2008)
US productivity growth surged twice post 1995 and post 2000. In contrast Germany registered two successive productivity reductions during that same period of time. Previous analysis of the post-2000 decline has been limited, however, by the short time series of the available data. In this paper we extend the Ifo Industry Growth Accounting Database that provides detailed industry-level investment information up to 2004. While much attention has focused on the reduction in German labor hours, our post-2000 data shows that a fledgling recovery in German non-ICT investment was offset by a widespread collapse in German total factor productivity. Almost half of German industries (accounting for over 45 percent of German output) did not experience positive TFP growth post 2000. Industries that constitute over a quarter of Germanys value-added exhibited negative labor productivity growth during the same period. The negative German productivity trend is thus continuing, which accelerates the countrys departure from the productivity frontier.
Keywords: L60; L80; O14; O47; 330; Growth accounting; industry productivity analysis; information and communication technology